2019
DOI: 10.1063/1.5094992
|View full text |Cite
|
Sign up to set email alerts
|

Reutealis trisperma press cake induced production of xylanase by Trichoderma reesei: Effect of C/N ratio and initial pH

Abstract: Edible coating chitosan and lycopene isolated from watermelon as a solution to extend fruit and vegetables storage time from after harvest damage

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The growth kinetic parameters (μ) obtained under the different fermentation conditions shown in Table were used for a statistical analysis to find out the effect of the aeration rate and the carbohydrate/protein ratio of the substrate on the growth rate, as presented in Table S1. The lowest growth rate was obtained in the case of the SSF with a SC:WB ratio of 3:1 and aeration of 1.9 VKgM because of the effects of the carbon and nitrogen ratios in the substrate, carbon content, and moisture evaporation causing a loss of water for growth . It was observed that the growth rate of T.…”
Section: Resultsmentioning
confidence: 96%
“…The growth kinetic parameters (μ) obtained under the different fermentation conditions shown in Table were used for a statistical analysis to find out the effect of the aeration rate and the carbohydrate/protein ratio of the substrate on the growth rate, as presented in Table S1. The lowest growth rate was obtained in the case of the SSF with a SC:WB ratio of 3:1 and aeration of 1.9 VKgM because of the effects of the carbon and nitrogen ratios in the substrate, carbon content, and moisture evaporation causing a loss of water for growth . It was observed that the growth rate of T.…”
Section: Resultsmentioning
confidence: 96%